Yellow Beach 2 after 75 years : the archaeology of a WWII invasion beach on Saipan and its historic context in the Commonwealth of the Northern Mariana Islands /: the archaeology of a WWII invasion beach on Saipan and its historic context in the Commonwealth of the Northern Mariana Islands. (2019) - Dixon, Boyd; Tenorio, Brenda Y; Walth, Cherie; Mowrer, Kathy
No abstract available